Clumpy dust rings around non-accreting young stars - Scholz, Aleks; Petkova, Maya A. (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We investigate four young, but non-accreting, very low mass stars in Orion, which show irregular eclipses by circumstellar dust. The eclipses are not
Gesehen am 18.02.2019